2017
DOI: 10.1002/hep.29189
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow–derived mesenchymal stromal cells for hepatitis B virus–related acute‐on‐chronic liver failure: A randomized controlled trial

Abstract: Peripheral infusion of allogeneic bone marrow-derived MSCs is safe and convenient for patients with HBV-related ACLF and significantly increases the 24-week survival rate by improving liver function and decreasing the incidence of severe infections. (Hepatology 2017;66:209-219).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
222
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(229 citation statements)
references
References 31 publications
5
222
0
2
Order By: Relevance
“…Patient populations were diverse and included cardiovascular (12 trials, n = 612 patients) [21,24À27,29,37,40,42,44,49,58], neurological (10 trials, n = 242 patients) [30À32, 36,45,48,57,62,65,69], renal (three trials, n = 177 patients) [55,63,67], liver (seven trials, n = 404 patients) [35,43,47,53,54,59,66], respiratory (three trials, n = 134 patients) [18,23,68] and endocrine diseases (four trials, n = 169 patients) [22,28,39,50], hematological/oncological malignancies (five trials, n = 318 patients) [33,34,41,46,71], immune deficient or inflammatory conditions (nine trials, n = 544 patients) [20,38,51,52,60,61,64,70,72], general frailty (one trial, n = 30 patients) [56], and severe sepsis in severely neutropenic patients with hematologic malignancies (one trial, n = 30 patients) [19].…”
Section: Resultsmentioning
confidence: 99%
“…Patient populations were diverse and included cardiovascular (12 trials, n = 612 patients) [21,24À27,29,37,40,42,44,49,58], neurological (10 trials, n = 242 patients) [30À32, 36,45,48,57,62,65,69], renal (three trials, n = 177 patients) [55,63,67], liver (seven trials, n = 404 patients) [35,43,47,53,54,59,66], respiratory (three trials, n = 134 patients) [18,23,68] and endocrine diseases (four trials, n = 169 patients) [22,28,39,50], hematological/oncological malignancies (five trials, n = 318 patients) [33,34,41,46,71], immune deficient or inflammatory conditions (nine trials, n = 544 patients) [20,38,51,52,60,61,64,70,72], general frailty (one trial, n = 30 patients) [56], and severe sepsis in severely neutropenic patients with hematologic malignancies (one trial, n = 30 patients) [19].…”
Section: Resultsmentioning
confidence: 99%
“…Although conventional antioxidants have beneficial roles in improving liver I/R injury, these reagents are not convenient for clinical application, largely because their effects and side effects are not fully understood 40 . UC-MSCs are considered as a promising therapeutic tool for several liver diseases [41][42][43][44][45] . This study also confirmed that UC-MSCs protected both liver tissue and L02 hepatocytes against I/R and H/R injury, as demonstrated by decrease of serum liver enzymes, alleviation of liver injury and reduced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MSCs derived from different tissues have the potential to alleviate hepatic IRI by suppressing oxidative stress and inhibiting hepatocellular apoptosis (13)(14)(15)(16)(17). Moreover, several clinical trials assessing the therapeutic efficacy of MSCs have reported positive outcomes for the treatment of graft-vs.-host disease in liver transplantation and acuteon-chronic liver failure (18,19). However, the major concern with the use of MSCs is related to their survival and multilineage differentiation potential in vivo, which might result in the formation of the wrong cell types and could even support the development of pre-existing tumors, so safety issues need to be taken into account when MSCs are used in humans (20).…”
mentioning
confidence: 99%